Transgenders in Kuantan, Pahang: knowledge and attitude towards HIV/AIDS - Draman, Samsul; Suofeiya, Maliya; Mohd Anuar, Muhamad Shaiful Lizam; Mohd Hussin, Muhammad Salman; Hisham, Mohamad Faqihuddin; Mohd Rus, Razman; Musa, Ramli (Research Management Centre, International Islamic University Malaysia, 2016)
Lack of knowledge and negative attitude towards HIV/AIDS may be the risk factors for HIV infection among transgenders. The researches done on knowledge and attitude towards HIV infection in transgender communities are very limited at both local and international levels. This study aimed to assess the knowledge and attitude on HIV infection among the male-to-female transgender community in Kuantan, Pahang. A crosssectional study was carried out from July to August in 2014 among 33 male-to-female transgenders in Kuantan, Pahang. Convenience sampling was used. Participants who gave consent answered a self-administered questionnaire. The data obtained was analyzed with descriptive statistics, χ 2 -test, and independent sample t test. Majority of the subjects in this study was 29 years and below (48.5%), Muslims (93.9%), and completed up to secondary education (60.6%). A higher percentage of them also sold sex (60.6%), and had relatively low income (from “no income” to RM 3000, mean = RM1528). 87.9% of the subjects demonstrated good knowledge and also positive attitude towards HIV/AIDS. Level of education was significantly associated with scores in knowledge (p=0.01). Despite the positive outcome from this study, misconceptions towards HIV/AIDS still exist among transgenders. Transgenders must not be rejected from receiving education. Their medical and spiritual needs must be addressed. Educations and interventions towards HIV/AIDS are desperately needed to deliver the correct information to this population, so as to emphasize prevention, early detection, and holistic medical care. Transgenders also require attentions from religious bodies and non-governmental organizations to provide help in employment, financial, spiritual, and psycho-social issues.